2014
DOI: 10.2298/gensr1403839p
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness of soybean genotypes based on agromorphological traits and RAPD markers

Abstract: Modern agriculture, breeding procedures, as well as competition among breeding institutions contribute to further reduction of already narrowed diversity of soybean commercial varieties. The objective of the study was to characterize eighteen soybean cultivars from three different breeding programs for agro-morphological traits and to reveal genetic diversity using molecular markers. Morphological description was performed with 13 qualitative and 9 quantitative traits. The genetic relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The varieties of this group with an average number of days to maturity (133), bred in this part of region have shown similar performance, which is in accordance with the findings of Vratarić and Sudarić (2008) that for this part of the region the optimal maturity group of soybean is from 130 to 135 days. It is also indicated in the conclusions of Ristova et al (2010) and Perić et al (2014). …”
Section: Methodsmentioning
confidence: 58%
“…The varieties of this group with an average number of days to maturity (133), bred in this part of region have shown similar performance, which is in accordance with the findings of Vratarić and Sudarić (2008) that for this part of the region the optimal maturity group of soybean is from 130 to 135 days. It is also indicated in the conclusions of Ristova et al (2010) and Perić et al (2014). …”
Section: Methodsmentioning
confidence: 58%
“…The identified character for each cluster depends on the genetic material used or is also determined by the origin of the gene source used. According to Peric et al (2014), a great similarity was usually found, primarily between the varieties come from the same institution because these varieties, generally, were developed from the same crosses.…”
Section: Discussionmentioning
confidence: 99%
“…This process, which Harlan [19] called genetic erosion, appears because of the replacement of diverse indigenous populations with modern, new, uniform cultivars and hybrids, and it causes a considerable threat to the production of food and hence the survival of humans. A narrow genetic base has been identified in most soybean germplasm studies [20,21]. However, Hahn and Würschum [22] noted that the genetic base of middle European genotypes was not as narrow as expected because of the unsystematic phenotype selection.…”
Section: Introductionmentioning
confidence: 99%